2019
DOI: 10.1002/jbm.b.34420
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemic condition influence on mineral trioxide aggregate biocompatibility and biomineralization

Abstract: This study aimed to investigate in vitro and in vivo the influence of hyperglycemic condition on biocompatibility and biomineralization of gray mineral trioxide aggregate (GMTA) and white mineral trioxide aggregate (WMTA). For the in vitro study, fibroblast‐like cells L929 were cultured under high or normal glucose concentration to investigate the effects of both MTA's on cell proliferation and inflammatory cytokines production IL‐1β, IL‐6, and TNF‐α. For the in vivo study, polyethylene tubes containing MTA ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…Moreover, cytokine secretion has been related to the concentration of Ambroxol administered [29]. Cytokine production depends on the cell type, sealer composition, and cytokines investigated [21,23,29]. Therefore, we believe that the undifferentiated cell line and the concentration of Ambroxol utilized may be the reason for this absence, and could therefore justify our findings.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Moreover, cytokine secretion has been related to the concentration of Ambroxol administered [29]. Cytokine production depends on the cell type, sealer composition, and cytokines investigated [21,23,29]. Therefore, we believe that the undifferentiated cell line and the concentration of Ambroxol utilized may be the reason for this absence, and could therefore justify our findings.…”
Section: Discussionsupporting
confidence: 53%
“…Deposition of mineralized tissue is associated with the ability of biomaterials to release Ca +2 ions [21]. Studies have shown that Ambroxol blocks calcium and sodium channels [38] and reduces the mineral percentage of calcium and phosphate in dentin [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations